14 GHz Schottky Diodes Using a p‐Doped Organic Polymer. Issue 22 (21st January 2022) - Loganathan, Kalaivanan; Scaccabarozzi, Alberto D.; Faber, Hendrik; Ferrari, Federico; Bizak, Zhanibek; Yengel, Emre; Naphade, Dipti R.; Gedda, Murali; He, Qiao; Solomeshch, Olga; Adilbekova, Begimai; Yarali, Emre; et al.
Abstract: The low carrier mobility of organic semiconductors and the high parasitic resistance and capacitance often encountered in conventional organic Schottky diodes hinder their deployment in emerging radio frequency (RF) electronics. Here, these limitations are overcome by combining self‐aligned asymmetric nanogap electrodes (≈25 nm) produced by adhesion lithography, with a high mobility organic semiconductor, and RF Schottky diodes able to operate in the 5G frequency spectrum are demonstrated. C16 IDT‐BT is used, as the high hole mobility polymer, and the impact of p ‐doping on the diode performance is studied. Pristine C16 IDT‐BT‐based diodes exhibit maximum intrinsic and extrinsic cutoff frequencies ( f C ) of >100 and 6 GHz, respectively. This extraordinary performance is attributed to the planar nature of the nanogap channel and the diode's small junction capacitance (<2 pF). Doping of C16 IDT‐BT with the molecular p ‐dopant C60 F48 improves the diode's performance further by reducing the series resistance resulting to intrinsic and extrinsic f C of >100 and ≈14 GHz respectively, while the DC output voltage of an RF rectifier circuit increases by a tenfold. Our work highlights the importance of the planar nanogap architecture and paves the way for the use of organic Schottky diodes in large‐area RF electronics of the future. Abstract : Combining asymmetric co‐planar nanogap electrodes with a p ‐doped organic polymer semiconductor yields Schottky diodes that are capable of operating at 14 GHz, making them the fastest organic electronic devices reported to date.